A single, early aged care experience improves speech-language pathology students' attitudes towards older people, communication confidence, and career aspirations in aged care. (4th May 2021) - Wallace, Sarah J.; Mathew, Akhila; Mandrusiak, Allison; Hatton, Anna
Abstract: Purpose: This study aimed to investigate if a single, early learning experience in an aged care setting could influence speech-language pathology students': (1) attitudes towards older people; (2) confidence in communicating with older people; and (3) career aspirations in aged care. Method: Ninety first-year undergraduate speech-language pathology students participated in a single visit to an aged care community centre. Students participated in recreational activities alongside older people and engaged in conversation. Before and after the visit, students completed surveys which examined their attitudes towards older people (UCLA Geriatrics Attitudes Scale) and self-perceived communication confidence. A Learning Reactionnaire, examining satisfaction with the experience and career aspirations, was completed post-visit. Quantitative data were analysed using descriptive statistics and non-parametric tests. Qualitative data were analysed using inductive content analysis. Result: Students demonstrated positive changes in their attitudes towards older people and increased communication confidence. Students reported increased interest in future employment in aged care. High satisfaction towards the learning experience was reported. Conclusion: These preliminary findings indicate that a single, early learning experience in an aged care setting can positively shape the attitudes and self-perceived communication skills of first-year speech-language pathology students and help foster interest in pursuing a career in aged care.